Antiviral Effect of Bovine Lactoferrin against Enterovirus E - Małgorzata Wróbel; Joanna Małaczewska; Edyta Kaczorek-Łukowska (Molecules, 2022)
Enterovirus E (EV-E), a representative of the Picornaviridae family, endemically affects cattle across the world, typically causing subclinical infections. However, under favorable conditions, severe or fatal disorders of the respiratory, digestive, and reproductive systems may develop. There is no specific treatment for enterovirus infections in humans or animals, and only symptomatic treatment is available. The aim of this study was to determine the in vitro antiviral effect of bovine lactoferrin (bLF) against enterovirus E using virucidal, cytopathic effect inhibition, and viral yield reduction assays in MDBK cells. The influence of lactoferrin on the intracellular viral RNA level was also determined. Surprisingly, lactoferrin did not have a protective effect on cells, although it inhibited the replication of the virus during the adsorption and post-adsorption stages (viral titres reduced by 1–1.1 log). Additionally, a decrease in the viral RNA level in cells (by up to 75%) was observed. More detailed studies are needed to determine the mechanism of bovine lactoferrin effect on enterovirus E. However, this highly biocompatible protein ensures some degree of protection against infection by bovine enterovirus, which is particularly important for young animals that receive this protein in their mother’s milk.